Interaksi Guru dan Siswa dalam Pembelajaran IPS di SMA Islam Abhariyah Jerneng Kab Lombok Barat - Saofiandi, Ari; Andayani, Endah; Rusfandi, Rusfandi (Jurnal Penelitian dan Pendidikan IPS, 2025)
This study aims to understand the interaction process between teachers and students in social studies (IPS) learning at SMA Islam Abhariyah Pagutan. The scope of this research includes the interaction patterns applied in learning, the factors influencing student engagement, and their impact on students' understanding of social studies material. This study employs a descriptive qualitative method with data collection techniques consisting of interviews, observations, and documentation. The results show that in social studies learning, teachers and students do not apply all four interaction models but only use two: the one-way learning model and, on certain occasions such as school exams, the two-way interaction model. The one-way learning model is the dominant choice because it is considered more suitable for students, who have a dual role as both learners and Islamic boarding school students. In conclusion, interaction in social studies learning at SMA Islam Abhariyah Pagutan is still dominated by a one-way communication pattern, which affects students' low engagement in the learning process. Therefore, more interactive teaching strategies are needed to encourage student participation and enhance their understanding of the material.